Changement et innovation en éducation : deux notions en résonance - Françoise Cros; Dominique Broussal
Change and innovation are terms often taken for each other. But this is not the case and this distinction is important in education and training, because it determines how to understand the evolution of education and training systems. This presentation aims to show the differences, both historically and socially. Change is more readily associated with support, while innovation focuses on the content of the transformation and its impacts. The concept of new is however common and it is in the treatment of this novelty and its realization that a possible comparison is made between the two terms. These two terms, which are widely used in training, are both factors of transformation: if change focuses on supporting career paths, innovation as an adventure puts more emphasis on the effects of change that it can produce in a short-term or long-term, on people, organisations and institutions. This contribution is an opening to reflection implemented in the articles of this thematic issue.